2019
DOI: 10.1111/cla.12384
|View full text |Cite
|
Sign up to set email alerts
|

A global plastid phylogeny of the fern genus Asplenium (Aspleniaceae)

Abstract: The infrageneric relationships and taxonomy of the largest fern genus, Asplenium (Aspleniaceae), have remained poorly understood. Previous studies have focused mainly on specific species complexes involving a few or dozens of species only, or have achieved a large taxon sampling but only one plastid marker was used. In the present study, DNA sequences from six plastid markers (atpB, rbcL, rps4, rps4-trnS, trnL and trnL-F) of 1030 accessions (616 of them newly sequenced here) representing c. 420 species of Aspl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
40
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 123 publications
(141 reference statements)
3
40
1
1
Order By: Relevance
“…PPG I, ). Based on the phylogenetic framework and exploration of morphological characters herein, and to maintain the monophyly of lineages that share diagnostic synapomorphies instead of producing homoplasy, Neolepisorus , Lemmaphyllum , Tricholepidium , Neocheiropteris , Lepidomicrosorium and Paragramma are treated as synonyms of Lepisorus ; a similar taxonomic strategy also is found in other large derived fern genera, such as Asplenium , Pteris , Diplazium and Dryopteris , that comprise lineages formerly treated as independent segregates (Zhang et al., , ; Wei et al., ; Xu et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…PPG I, ). Based on the phylogenetic framework and exploration of morphological characters herein, and to maintain the monophyly of lineages that share diagnostic synapomorphies instead of producing homoplasy, Neolepisorus , Lemmaphyllum , Tricholepidium , Neocheiropteris , Lepidomicrosorium and Paragramma are treated as synonyms of Lepisorus ; a similar taxonomic strategy also is found in other large derived fern genera, such as Asplenium , Pteris , Diplazium and Dryopteris , that comprise lineages formerly treated as independent segregates (Zhang et al., , ; Wei et al., ; Xu et al., ).…”
Section: Discussionmentioning
confidence: 99%
“… wrightii could be easily identified and are distinguishable from one another, based on morphological characteristics and geographical distribution. Our recent global phylogeny of Asplenium ( Xu et al 2020 ) supports both A. alatulum and A.…”
Section: Introductionmentioning
confidence: 63%
“… matsumurae were found not to be closely related to the A. wrightii complex in a phylogenetic study ( Xu et al 2020 ). The A.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A. nidus is a well-known C3 epiphytic fern, and phylogenetic analyses have revealed that it belongs to the Neottopteris clade, which is the sister of the Phyllitis clade containing the terrestrial species A. komarovii ( A. scolopendrium L. subsp. Japonicum ) [911]. These two species have considerable similarities in morphology, including the presence of lanceolate simple leaves spirally tightly clustered into a bird's nest fern.…”
Section: Introductionmentioning
confidence: 99%